The Relationship Between New Ways of Working and Employee Engagement: First and Foremost a Matter of Environment Fit - David Giauque; Frédéric Cornu; Samuel Pacht (Administrative Sciences)
Working independently of a fixed schedule or specific place while staying connected with colleagues and managers via digital technologies is the cornerstone of new ways of working (NWW). Following the COVID-19 crisis, these have become more popular and more extensively used. The main objective of this article is to find out more about the factors that positively influence the use of NWW and to investigate whether their use can have an impact on employees’ work engagement. We employ person–environment fit (P–E fit) theory to link our different variables, emphasizing that a good fit between an individual and their work environment is the driving force linking NWW and work engagement. Our questionnaire survey (n = 2693) demonstrates that NWW does not directly influence work engagement but only does so indirectly through P–E fit. We also prove that a climate of trust, a result-oriented culture, and specific work characteristics can act as positive levers in the deployment of NWW and positively influence P–E fit. This study makes both empirical and theoretical contributions to the NWW literature.